2002
DOI: 10.1183/09031936.02.00262102
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos bodies in the sputum of asbestos workers: correlation with occupational exposure

Abstract: A cross-sectional medical survey including collection of three consecutive sputum samples was carried out among 270 retired workers of a textile and friction materials factory, in order to investigate the relationship between asbestos body identification and asbestos exposure.The individual cumulative asbestos exposure, determined by means of a plant-specific job-exposure matrix based on asbestos air measurements in the workshops, proved to be heavy with a mean cumulative exposure of 217 fibres?mL -1 6yr. Macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…The current results are consistent with the hypothesis that cumulative exposure is more important than TSFE for the development of asbestosis [4], as no significant relationship was observed for TSFE in adjusted models. These results are in accordance with biological data on retention of asbestos [24]. However, although significant correlations were observed between CEI (or level of exposure) and asbestosis, these correlations appeared to be weak.…”
Section: Occupational and Environmental Lung Disease C Paris Et Alsupporting
confidence: 81%
“…The current results are consistent with the hypothesis that cumulative exposure is more important than TSFE for the development of asbestosis [4], as no significant relationship was observed for TSFE in adjusted models. These results are in accordance with biological data on retention of asbestos [24]. However, although significant correlations were observed between CEI (or level of exposure) and asbestosis, these correlations appeared to be weak.…”
Section: Occupational and Environmental Lung Disease C Paris Et Alsupporting
confidence: 81%
“…A cumulative exposure index, expressed in fibers/ ml  years was therefore calculated for each subject by determining the sum of the products [exposure  duration] characterizing each job position, as previously described [Paris et al, 2002].…”
Section: Study Populationmentioning
confidence: 99%
“…However, a sputum sample positive for asbestos bodies is suggestive of a high lung asbestos burden, since a correlation has only been found in workers with high levels of exposure [20,21]. Although another group of investigators found agreement of asbestos body detection in only 56.8% of their cases, they concluded that the two methods (BAL+IS) were complementary, since both are useful in increasing the probability of detection [22].…”
Section: Exposure Assessmentmentioning
confidence: 99%